PENGARUH MINUMAN SARI JAHE DALAM MENGURANGI EMESIS GRAVIDARUM PADA IBU HAMIL DI PUSKESMAS ALAK - DINA MS HENUKH (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
ABSTRACT A inconvenience that often occurs in pregnant women is emesis gravidarum. Emesis gravidarum is generally experienced by 65-70% of pregnant women, often occurring in 60-80% primigravida and 40-60% multigravida. Where as hyperemesis gravidarum occurs around 10-15%. When pregnant the gastric works more slowly in digesting food than before pregnancy so it can trigger vomiting. The aromatic essential oil content and spicy gingerol taste in ginger can have a direct influence on the digestive tract. The purpose of this study is to determine whether there is an effect of ginger juice drinks in reducing emesis gravidarum in pregnant women. The research design used Pre Experimental with the design of the One Group Pretest Posttest. The number of samples in this study were 16 people, with a purposive sampling method. Measurements were made before and after being given ginger juice drinks for 4 days with an observation sheet. The results of the Wilcoxon test showed that there was an effective decrease in the emesis of gravidarum in pregnant women after giving ginger juice drinks to pregnant women in Alak Public Health Center in 2018 with a ρ-value of 0.001 (α = 0.05).. Keywords: Emesis gravidarum, ginger, pregnancy